THE THEORETICAL AND PRACTICAL SIGNIFICANCE OF ORGANIZING STUDENTS’ INDEPENDENT LEARNING ACTIVITIES BASED ON MODERN EDUCATIONAL TOOLS (Multidisciplinary Journal of Science and Technology, 2026)
This article explores the theoretical and practical significance of organizing students’ independent learning activities based on modern educational tools. The study analyzes contemporary approaches to independent learning, highlights the role of digital technologies and innovative pedagogical methods, and examines their impact on students’ cognitive development and academic performance. The paper also identifies key challenges and proposes effective strategies for enhancing independent learning in higher education institutions.